Experimental analysis of a diesel engine operating in diesel-ethanol dual-fuel mode - Roberto Freitas Britto Júnior (2014)
A significant part of the world economy depends on stationary or vehicular Diesel engines. Such engines are fed mainly by fossil fuels, among these, the standard diesel. The growing interest in renewable energy sources makes the use of ethanol in these engines a real technological demand. From the existing concepts to meet this goal the Diesel-Ethanol in the Dual-Fuel mode has demand for published experimental data. Such concept brings a greater degree of freedom, but implications in technological challenges. It works through a PFI (Port Fuel Injection) system to prepare a pre-mixture of air and ethanol in the intake port which is compressed in the combustion chamber and ignited by pilot injection of diesel. In this work a single cylinder research engine with 100% electronically controlled calibration was used. The engine control parameters were set to maximize diesel substitution rate by ethanol with a limited indicated efficiency loss. Comparisons were made among different working conditions. Initially, the flow structure in the combustion chamber was tested in both quiescent and high swirl modes. Compression ratios were adjusted at 3 different levels: 14:1, 16:1 and 17:1. Two injectors were tested, the first one with mass flow of 35 g/s and another of 45 g/s. Regarding pressure diesel injection, 4 levels were investigated namely 800, 1000, 1200 and 1400 bar. The experiments discussed in this work were able to achieve up to 65% of diesel energy substituted by hydrated ethanol energy with an indicated efficiency of 49%. In comparison with the diesel only running condition, the NOx emissions was improved by up to 60%. But the HC, CO and aldehydes emissions had a penalty, showing a trade-off that shall be further investigated with a final design engine in the beginning of product development process.